2014
DOI: 10.1038/nmat3873
|View full text |Cite
|
Sign up to set email alerts
|

Movable high-Q nanoresonators realized by semiconductor nanowires on a Si photonic crystal platform

Abstract: Sub-wavelength semiconductor nanowires have been attracting strong interest recently for photonic applications because they possess various unique optical properties and offer great potential for miniaturizing devices. However, with these nanowires, it is not easy to realize tight light confinement or efficient coupling with photonic circuits. Here we show that a high Q nanocavity can be created by placing a single III/V semiconductor nanowire with the diameter less than 100 nm in a grooved waveguide in a Si p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 46 publications
4
118
0
Order By: Relevance
“…This means that a suitable design for the nanowire and PhC cavity can allow a substantial reduction of the lasing threshold of the nanowire and also raise the spontaneous emission factor to~0.3, which is a typical number for nanolasers [52]. The group of Notomi at Nippon Telegraph and Telephone (NTT) in Japan managed recently to show the Purcell effect in a single InAsP nanowire on top of an Si photonic crystal, but no lasing was observed [12].…”
Section: (D) External Cavity Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that a suitable design for the nanowire and PhC cavity can allow a substantial reduction of the lasing threshold of the nanowire and also raise the spontaneous emission factor to~0.3, which is a typical number for nanolasers [52]. The group of Notomi at Nippon Telegraph and Telephone (NTT) in Japan managed recently to show the Purcell effect in a single InAsP nanowire on top of an Si photonic crystal, but no lasing was observed [12].…”
Section: (D) External Cavity Engineeringmentioning
confidence: 99%
“…This leads to much simpler and stronger light-matter coupling; however, individual nanowires must be placed one by one in the cavity [11,12]. This approach was very recently investigated at NTT in Japan.…”
Section: (D) External Cavity Engineeringmentioning
confidence: 99%
“…Semiconductor nanowires form an important building block for nanophotonic devices, as their growth is well controlled using a variety of top-down and bottom-up techniques [1,2]. The quasi-one dimensional geometry of a nanowire enables their use as antennas and cavities for light [3][4][5][6][7][8][9][10], and offers many advantages for applications such as photodetectors [11][12][13][14][15], solar cells [16][17][18], and single photon sources [19]. Optimization of such devices requires knowledge of the nanostructured materials at a more fundamental level.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The most recent studies have shown that bent nanowires or nanobelts can exhibit novel optical and electrical properties compared with their unbent counterparts, thus appreciably widening their potential applications in optoelectronic systems because optoelectronic characteristics in lowdimensional materials are particularly sensitive to crystallinity and electronic structures. 3 For example, in the photoluminescence spectra of bending wurtzite micro/nanowires, a red shift of the near-band energy induced by deformation has been shown to have a linear relation between the peak shift and the strain gradient.…”
Section: Introductionmentioning
confidence: 99%